Rapid Determination of 107 Illegally Added Nafils in Foods by Ultra-high Performance Liquid Chromatography-High Resolution Mass Spectrometry - FENG Feng, CHANG Qizhi, SUN Xiao, DU Rongzhu, ZHANG Feng (Shipin Kexue, 2025)
A rapid method for the determination 107 illegally added nafils in compressed candies, honey and beverage was developed by ultra-high performance liquid chromatography coupled with quadrupole orbitrap high-resolution mass spectrometry. The samples were extracted with methanol and separated on a Waters Acquity UPLC BEH C18 column (2.1 mm × 100 mm, 1.7 μm) with gradient elution using a mobile phase consisting of acetonitrile and 0.1% formic acid in water. The detection was conducted in both positive and negative ion modes, and a full MS scan/data dependent MS2 mode was used to collect data. The 107 nafils showed good linearity in the concentration range of 4–300 μg/L, with correlation coefficients (R2) greater than 0.99. The limits of detection (LODs) were 0.1–1 mg/kg, and the limits of quantification (LOQs) were 0.2–2 mg/kg. The average recoveries ranged from 82.5% to 117.0% at three spiked levels of 2, 5, 10 mg/kg, with relative standard deviations of 0.9%–10.0% (n = 6). This method was fast, accurate, sensitive, and suitable for the rapid identification and quantification of illegal additives in foods.